ANTHROPOMETRIC ANALYSIS AND BODY SCULPT IMPROVEMENT IN APPLICATION TO FEMALE STUDENTS FROM CHEERLEADING PICKED TEAMS - Timofeeva, O.V.; Lubyshev, E.A.; Ibragimova, N.A.; Vyprikov, D.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and experimentally substantiate a customized strength training block to improve body sculpt. Methods and structure of the study. An anthropometric analysis reliably reveals a correlation between the height to body-weight ratio, circumferential dimensions, skin-fat thickness, and body proportionality, and is, therefore, an integral indicator of the female body shape. Given that female students from picked teams perform at sports events in the presence of a large number of spectators, a customized strength training block aimed to improve body sculpt was included in the training sessions and used three times a week for 40 minutes. More strength exercises were used on the torso muscles (abs, oblique muscles), legs (lateral, inner, back and front of the thigh) and glutes. These exercises were performed at a rapid pace, for 1 minute per area, at HR of 140-150 bpm. The study was carried out at two Moscow higher educational establishments –Peoples' Friendship University of Russia and Plekhanov Russian University of Economics - in the conditions of training activities 3 times a week and lasted 1 academic year. Results and conclusion. The anthropometric analysis of the body shape made it possible to develop a customized strength training block aimed to improve the body sculpt of the female students from the cheerleading picked teams. It was proved to contribute to statistically significant changes in the anthropometric indices, improvement of female students’ physical fitness and body correction, and thus, beneficial for their physical appeal.